Political reality of local government service provision in the Free State Province - Boshoff, Willem Hendrik (Bloemfontein : Central University of Technology, Free State, 2011)
The Constitution of the Republic of South Africa, No. 108 of 1996 (SA, 1996) brought about a new system of government comprised of the national, provincial and local government spheres. In terms of the Constitution, these spheres of government must establish effective, transparent and accountable government. Local government is specifically responsible for the provision of democratic and accountable government to local communities, and for ensuring that municipal services are rendered to the community. As in the case of the national and provincial spheres of government, local government has a distinctive political nature and character. Councillors are elected to represent the voters who participate in municipal elections, as well as the relevant political parties, on municipal councils. The decisions of municipal councils are influenced by political considerations, as well as by the policy directives of the ruling party. The Constitution also establishes and describes the various governmental bodies that exercise the powers of the state. These governmental bodies represent the state and can be classified in terms of three primary groups, namely legislative, executive and legal structures. In a bona fide democracy, the doctrine of separation of powers, also known as the trias politica, is of fundamental importance in order to prevent autocracy and ensure civil liberty. The provision of viable municipal services is the most crucial reason for the existence of local government. The community has a legitimate expectation with regard to the provision of appropriate municipal services; and in terms of the Municipal Systems Act, No. 32 of 2000 (SA, 2000c) municipalities must supply basic municipal services in order to ensure an acceptable quality of life. However, inadequate levels of municipal service provision are encountered in South Africa in general, and in the Free State in particular. Such inadequate service provision has led to several violent community-protest actions in the country. These protests are an indication that municipal service provision does not meet the expectations of the communities. Various factors tend to have a negative effect on local government in the Free State, including capacity shortages, such as the lack of professional and experienced staff; financial shortages; and the extensive quantity and complexity of local government legislation. Political challenges that influence local government service provision include factors such as the absence of the political will to provide services, political in-fighting within the ruling party, the selection criteria for the appointment of municipal employees, and political interference in municipal administration. It is also essential that the ruling party should put acceptable mechanisms in place to ensure that the public sector becomes an effective instrument for carrying out the ruling party‟s mandate, rather than allowing political interference to affect the day-to-day activities of government. In order to meet the needs of the community with regard to service provision, it is essential that the three spheres of government should function as a coherent unit. Intergovernmental relations therefore play a central role in ensuring that the joint functions of government are effectively carried out. The national and provincial departments have a specific responsibility to support and strengthen local government capacity, and also to ensure the effective execution of municipal functions. However, various intergovernmental challenges need to be dealt with, namely ineffective co-ordination and integration, as well as the absence of the political will to promote intergovernmental relations. Therefore, the aim of this study is to identify specific actions and strategies that can be implemented by the government in order to address the challenges that have a negative influence on local government service provision, with specific reference to the political challenges.
Thesis (D. Tech.(Public Management)) -- Central University of Technology, free State, 2011
Keywords: Central University of Technology, Free State - Dissertations; Local government - South Africa - Free state - Administration; Municipal services - South Africa - Free State; Dissertations, academic - South Africa - Bloemfontein; Free State (South Africa) - Politics and government